Continuous Flow Left Ventricular Assist Device Implant Significantly Improves Pulmonary Hypertension, Right Ventricular Contractility, and Tricuspid Valve Competence. Issue 6 (30th September 2013) - Atluri, Pavan; Fairman, Alexander S.; MacArthur, John W.; Goldstone, Andrew B.; Cohen, Jeffrey E.; Howard, Jessica L.; Zalewski, Christyna M.; Shudo, Yasuhiro; Woo, Y. Joseph
Abstract Background Continuous flow left ventricular assist devices (CF LVAD) are being implanted with increasing frequency for end‐stage heart failure. At the time of LVAD implant, a large proportion of patients have pulmonary hypertension, right ventricular (RV) dysfunction, and tricuspid regurgitation (TR). RV dysfunction and TR can exacerbate renal dysfunction, hepatic dysfunction, coagulopathy, edema, and even prohibit isolated LVAD implant. Repairing TR mandates increased cardiopulmonary bypass time and bicaval cannulation, which should be reserved for the time of orthotopic heart transplantation. We hypothesized that CF LVAD implant would improve pulmonary artery pressures, enhance RV function, and minimize TR, obviating need for surgical tricuspid repair. Methods One hundred fourteen continuous flow LVADs implanted from 2005 through 2011 at a single center, with medical management of functional TR, were retrospectively analyzed. Pulmonary artery pressures were measured immediately prior to and following LVAD implant. RV function and TR were graded according to standard echocardiographic criteria, prior to, immediately following, and long‐term following LVAD. Results There was a significant improvement in post‐VAD mean pulmonary arterial pressures (26.6 ± 4.9 vs. 30.2 ± 7.4 mmHg, p = 0.008) with equivalent loading pressures (CVP = 12.0 ± 4.0 vs. 12.1 ± 5.1 p = NS). RV function significantly improved, as noted by right ventricular stroke work index (7.04 ± 2.60 vs. 6.05 ± 2.54, p = 0.02). There was an immediate improvement in TR grade and RV function following LVAD implant, which was sustained long term. Conclusion Continuous flow LVAD implant improves pulmonary hypertension, RV function, and tricuspid regurgitation. TR may be managed nonoperatively during CF LVAD implant. doi: 10.1111/jocs.12214 (J Card Surg 2013;28:770–775)